Obtenção de ésteres graxos de sacarose a partir do óleo das sementes de Carica papaya L. - Bernardi, Alberto Carlos; Vilegas, Wagner; Cabrera, Álvaro; Pozetti, Gilberto Luiz (Eclética Química, 1994)
.